Ecological and genomic vulnerability to climate change across native populations of Robusta coffee ( Coffea canephora ) - Rémi Tournebize; Leyli Borner; Stéphanie Manel; Christine N. Meynard; Yves Vigouroux; Dominique Crouzillat; Coralie Fournier; Mohamed Kassam; Patrick Descombes; Christine Tranchant‐Dubreuil; Hugues Parrinello; Catherine Kiwuka; et al. (Global Change Biology, 2022)
The assessment of population vulnerability under climate change is crucial for planning conservation as well as for ensuring food security. Coffea canephora is, in its native habitat, an understorey tree that is mainly distributed in the lowland rainforests of tropical Africa. Also known as Robusta, its commercial value constitutes a significant revenue for many human populations in tropical countries. Comparing ecological and genomic vulnerabilities within the species’ native range can provide valuable insights about habitat loss and the species’ adaptive potential, allowing to identify genotypes that may act as a resource for varietal improvement. By applying species distribution models, we assessed ecological vulnerability as the decrease in climatic suitability under future climatic conditions from 492 occurrences. We then quantified genomic vulnerability (or risk of maladaptation) as the allelic composition change required to keep pace with predicted climate change. Genomic vulnerability was estimated from genomic environmental correlations throughout the native range. Suitable habitat was predicted to diminish to half its size by 2050, with populations near coastlines and around the Congo River being the most vulnerable. Whole‐genome sequencing revealed 165 candidate SNPs associated with climatic adaptation in C. canephora , which were located in genes involved in plant response to biotic and abiotic stressors. Genomic vulnerability was higher for populations in West Africa and in the region at the border between DRC and Uganda. Despite an overall low correlation between genomic and ecological vulnerability at broad scale, these two components of vulnerability overlap spatially in ways that may become damaging. Genomic vulnerability was estimated to be 23% higher in populations where habitat will be lost in 2050 compared to regions where habitat will remain suitable. These results highlight how ecological and genomic vulnerabilities are relevant when planning on how to cope with climate change regarding an economically important species.

Adaptive potential of Coffea canephora from Uganda in response to climate change - Sinara Oliveira de Aquino; Catherine Kiwuka; Rémi Tournebize; Clément Gain; Pierre Marraccini; Cédric Mariac; Kévin Bethune; Marie Couderc; Philippe Cubry; Alan C. Andrade; Maud Lepelley; Olivier Darracq; et al. (Molecular Ecology, 2022)
Understanding vulnerabilities of plant populations to climate change could help preserve their biodiversity and reveal new elite parents for future breeding programmes. To this end, landscape genomics is a useful approach for assessing putative adaptations to future climatic conditions, especially in long‐lived species such as trees. We conducted a population genomics study of 207 Coffea canephora trees from seven forests along different climate gradients in Uganda. For this, we sequenced 323 candidate genes involved in key metabolic and defence pathways in coffee. Seventy‐one single nucleotide polymorphisms (SNPs) were found to be significantly associated with bioclimatic variables, and were thereby considered as putatively adaptive loci. These SNPs were linked to key candidate genes, including transcription factors, like DREB ‐like and MYB family genes controlling plant responses to abiotic stresses, as well as other genes of organoleptic interest, such as the DXMT gene involved in caffeine biosynthesis and a putative pest repellent. These climate‐associated genetic markers were used to compute genetic offsets, predicting population responses to future climatic conditions based on local climate change forecasts. Using these measures of maladaptation to future conditions, substantial levels of genetic differentiation between present and future diversity were estimated for all populations and scenarios considered. The populations from the forests Zoka and Budongo, in the northernmost zone of Uganda, appeared to have the lowest genetic offsets under all predicted climate change patterns, while populations from Kalangala and Mabira, in the Lake Victoria region, exhibited the highest genetic offsets. The potential of these findings in terms of ex situ conservation strategies are discussed.

Developing core collections to optimize the management and the exploitation of diversity of the coffee Coffea canephora - Thierry Leroy; Fabien De Bellis; Hyacinthe Legnate; Pascal Musoli; Adrien Kalonji; Rey Gastón Loor Solórzano; Philippe Cubry (Genetica, 2014)

Inheritance of resistance to coffee wilt disease (Fusarium xylarioides Steyaert) in Robusta coffee (Coffea canephora Pierre) and breeding perspectives - Pascal C. Musoli; Christian Cilas; David Pot; Agnes Nabaggala; Saleh Nakendo; James Pande; André Charrier; Thierry Leroy; Daniel Bieysse (Tree Genetics & Genomes, 2013)

Global analysis of Coffea canephora Pierre ex Froehner (Rubiaceae) from the Guineo-Congolese region reveals impacts from climatic refuges and migration effects - Philippe Cubry; Fabien De Bellis; David Pot; Pascal Musoli; Thierry Leroy (Genetic Resources and Crop Evolution, 2013)